Development of a bulb onion topping tool - Pérez-Rodríguez, Claudia Patricia (2019)
Bulb onion, an important product in the diet of Colombians, has an annual production of approximately 53,497 tons in Cundinamarca; after harvesting it is necessary to eliminate pseudostems and roots, by means of a procedure called “espatado”. Within the subproject “Technologies and design or redesign of products that support the logistics operation system and distribution and development of a model in Bogotá and Cundinamarca”, the need to develop a topping formal tool for bulb onion that responds not only to improve the effectiveness of the process and ergonomic conditions, but also reduce the risk of accidents at work allowing an adequate handling of the product that results in its quality was evident. For the design of this tool, the disciplines of agricultural engineering and industrial design were integrated. The methodology of the process included the identification of referents and determinants, definition of a concept and the construction of an initial model validated in the field. It was linked to the final design of the tool, the feedback of the producers in order to give an integral response to their needs. The use of the tool reduced the time to perform the task, going from 27.75 to 31.5 onions / minute, improved grip, facilitated the completion of the task, improved posture and decreased the risk of physical damage to the product.